PENINGKATAN KESEJAHTERAAN MULTIDIMENSIONAL LANSIA HIPERTENSI MELALUI PROGRAM SENIKEL DI GADING KARYA, SURABAYA - Orizani, Chindy Maria; Firmansyah, Yura Witsqa; Tjokro, Silvia Haniwijaya (PPM STIKES Adi Husada, 2025)
Introduction & Aim: Hypertension was one of the most common degenerative diseases among the elderly and could reduce their quality of life if not properly managed. This community service aimed to improve the multidimensional wellness of elderly with hypertension through the SENIKEL (Healthy, Energetic, Comfortable, Inspirational) program in RW 07 Gading Karya, Gading Sub-district, Tambaksari District, Surabaya City. Method of Activity: The method used health education, participatory discussion, and relaxation practice involving 35 elderly people with the criteria of having good cognitive abilities, being cooperative, and willing to participate in the activities until completion, which were carried out on December 27, 2024. Results: The results showed an increase in multidimensional wellness after the intervention. Before education, elderly in the good category of wellness were only 40.0%, increasing to 62.9% after the intervention. Meanwhile, the fair category decreased from 45.7% to 28.6%, and the poor category decreased from 14.3% to 8.6%. Discussion: This activity proved that community-based educational programs were effective in improving the holistic quality of life of elderly with hypertension. It was recommended that similar programs be carried out continuously with the support of health cadres and families to maintain the sustainability of the outcomes.